Itinerário Terapêutico de familiares de Crianças e Adolescentes com Necessidades Especiais de Saúde: Revisão integrativa - SANTOS, Adriana Torres dos (2022)
Children and Adolescents with Special Health Needs (CSHCN) represent a group that demands differentiated, complex and continuous health care. They are classified according to the health care demand presented, in which the plurality of care for CSHCN after discharge is a challenge and impacts all family members. In this sense, the National Primary Care Policy recommends that primary care be viewed as the preferred gateway, responsible for organizing and coordinating the interaction between all health services. The study aimed to investigate the scientific production regarding the therapeutic itinerary of family members of CSHCN in the search for comprehensive health care. This is an integrative review carried out in the following databases: Latin American and Caribbean Literature on Health Sciences (LILACS), Medical Literature Analysis an Retrieval System on-line (MEDLINE), Nursing Database (BDENF), Web Of Science, EMBASE, SciElo and SCOPUS, in the period from January to February 2022, the structuring of the research question was guided by the PECOS strategy and inclusion criteria were applied for the selection of studies, with no limited time for publication of articles . The Integrative Review retrieved 8 articles from the databases, they were subjected to critical analysis and three points of discussion were formulated, namely: The therapeutic itinerary of family members of CSHCN in the Health Care Networks observed in the fragility of Primary Health Care, low availability of care in health services, absence of care flows in Health Care Networks; Main barriers faced by family members of CSHCN in the therapeutic itinerary represented by the lack of preparation of the health team, mainly related to the transfer of information to the family and regarding the diagnostic investigation, lack of bonds between these professionals and the families, failures in the application of the principles of SUS, lack of dialogue between the services of the different management spheres; and, the CSHCN Political Invisibility Process. This Integrative Review showed that the lack of specific care flows for this clientele is responsible for the pilgrimage of families, making access to specialized health services a challenging process, since the search for care in primary care is sometimes replaced by private services. and the course is permeated by situations that make care for CSHCN unfeasible. As soon as primary care is no longer seen as a preferential gateway, the process of political invisibility becomes even more marked.